Bullying, family cohesion, and school connectedness: a moderated-mediation multigroup analysis of adolescents. Issue 2 (3rd April 2021) - Hawkins, Lindsey G.; Brown, Cameron C.; Goad, Chloe; Rhynehart, Abby; Hemphill, Taralyn; Snyder, Hailey
ABSTRACT: Bullying experiences in adolescence has become a nationwide problem as 28% of the children report being bullied over the past school year. Adolescents who report being bullied have been found to have higher rates of anxiety and depression. Although several studies have examined family support and school connectedness as protective factors that buffer the link between being bullied and mental health, little is known about racial/ethnic differences in bullying victimization. Bronfenbrenner's ecological systems theory proposes that a child's environment (e.g., family cohesion, school connectedness) is a potential protective factor between bullying experiences and mental health. Adolescent data from the Fragile Families and Child Wellbeing Study were used to analyze a structural model, postulating frequency of being bullied on the adolescents reports of perceived health, directly and as mediated by anxiety symptoms, was assessed among adolescents who were Black/African American, Hispanic/Latino, White, Multiracial, and other races not specified in the assessment. Additionally, we examined whether reports of family cohesion and/or school connectedness moderate the link between frequency of being bullied and anxiety. Modest, yet significant results indicated that there were group differences for the model, and school connectedness was linked with lower rates of anxiety symptoms and better reports of perceived health for most groups. These findings provided insight into the importance of considering contextual factors such as race when examining bullying victimization as well as provides insight for school and helping professionals such as family therapists striving to stymie the effects of being bullied among adolescents.